Perceptions of Turkish construction firms about the marketing concepts - Erdis, Ercan; Coskun, Hilmi; Demirci, Mustafa (Technological and Economic Development of Economy, 2015)
Competitive marketing environment requires construction companies to come up with the right strategies to progress. This only becomes possible by preparing rigorous preconstruction feasibility studies. Additionally, the effectiveness of promotion activities of the company is important to acquire a market share which can be realized by having systematic marketing concept. In this study, the perception and application level of marketing concept of construction firms are investigated. The promotion strategies which enable the companies to have systematic applications of marketing concepts in order to compete with other companies in the sector are discussed. To evaluate the marketing attitudes as applied by the companies, a questionnaire was performed with forty nine Turkish construction firms. The perception and application of the marketing are discussed based on the organizational structure and key interest areas of construction companies. The overall result deduced is that the construction companies do not have a systematic approach to marketing. The companies have primarily adopted the approaches to keep their current places in the sector.